Measuring immigration's effects on labor demand: a reexamination of the Mariel Boatlift - Örn B. Bodvarsson; Joshua J. Lewer; Hendrik F. van den Berg (Institute for the Study of Labor (IZA), 2007)
It is now well known that exogenous immigration shocks tend to have benign effects on native employment outcomes, thanks to various secondary adjustment processes made possible by flexible markets. One adjustment process that has received scant attention is that immigrants, as consumers of the goods they help produce, contribute to their own demand. We examine the effects of an immigration shock on labor demand by testing a general equilibrium model in which imperfectly substitutable native and immigrant workers spend their wages on a locally produced good. The shock induces three responses: (i) a substitution of immigrants for natives; (ii) out-migration; and (iii) stimulation of labor demand. According to (iii), native wages can fall, stay the same or rise, depending upon the strength of the shock and various product and factor market elasticities. As our test case, we reexamine the 1980 Mariel Boatlift, using Wacziarg's Channel Transmission methodology. Our data set includes approximately 6,600 observations for 1979-85 from the Current Population Survey on workers in 9 different retail labor markets and Survey of Buying Power data on retail spending by consumers in Miami and four comparison cities. Our results provide a more complete explanation for why the Boatlift's overall effects on native wages in Miami were benign: Lower wages due to greater labor supply were offset by higher wages due to greater labor demand. We conclude that the demand-augmenting effect of an immigration shock is a significant secondary adjustment process that must be considered when assessing the distributional effects of immigration.
Keywords: 330; Einwanderung; Schock; Arbeitsangebot; Gesamtwirtschaftliche Nachfrage; Arbeitsnachfrage; Lohnniveau; Allgemeines Gleichgewicht; Theorie; Flüchtlinge; Miami (Fla.)